Use of Tyvek Sheet as Microbial Filter Patch for Preparing Grain Spawn of Button Mushroom - Patwal, Naveen (Mushroom Research, 2021)
Tyvekis a nonwoven HDPE synthetic fiber and the name is a registered trademark of the DuPont Company (DuPont 2021). Â Because of its unique properties like lightweight, durable and breathable, yet resistant to water, abrasion, bacterial penetration and aging, it has many uses in daily Life. For example, most of the times important documents are shipped by courier company in a Tyvek envelope. Tyvek coveralls are one-piece garments, usually white, commonly worn by mechanics, oil industry workers, painters, and laboratory and clean-room workers. It is difficult to tear but can easily cut with scissor or knife. Fibers in Tyvek fabric are 0.5- 10 Âµm (compared to 75Â Âµm for a human hair) which allows only water vapour/gases to pass through, but liquid water cannot pass through it. Its fibers, bonded by heat and pressure, lead to this unique structure that gives Tyvek greater resistance to microbial penetration. It has neutral PH and is dimension stable and autoclave safe. These properties make Tyvek to be a suitable choice as microbial filter patch for spawn production.